2021
DOI: 10.1016/j.chest.2020.08.2104
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone Biosensor With App Meets FDA/ISO Standards for Clinical Pulse Oximetry and Can Be Reliably Used by a Wide Range of Patients

Abstract: Background Millions of smartphones contain a photoplethysmography (PPG) bio-sensor (Maxim Integrated, San Jose CA) that accurately measures pulse oximetry. No clinical use of these embedded sensors is currently being made, despite the relevance of remote clinical pulse oximetry to the management of chronic cardiopulmonary disease, and the triage, initial management and remote monitoring of persons effected by respiratory viral pandemics, such as SARS-CoV-2 or Influenza. To be used for clinical pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 19 publications
0
17
0
1
Order By: Relevance
“…Most recently, Browne et al reported findings from clinical studies on 320 participants that utilized a repeated measure, nested factorial design to evaluate the accuracy and precision of a smartphone model, containing Maxim Integrated biosensors and App in comparison to Welch Allyn reference units. 24 Their results indicated a wide range of adult persons utilized a smartphone model to perform repeated pulse oximeter spot checks with an accuracy and precision equivalent to hospital grade clip sensors. 24 This clinical study had few hypoxemic patients, but did report human steady state hypoxia testing of the smartphone model versus a portable reference device that indicated FDA/ISO requirements were likely to be met if full testing was conducted.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Most recently, Browne et al reported findings from clinical studies on 320 participants that utilized a repeated measure, nested factorial design to evaluate the accuracy and precision of a smartphone model, containing Maxim Integrated biosensors and App in comparison to Welch Allyn reference units. 24 Their results indicated a wide range of adult persons utilized a smartphone model to perform repeated pulse oximeter spot checks with an accuracy and precision equivalent to hospital grade clip sensors. 24 This clinical study had few hypoxemic patients, but did report human steady state hypoxia testing of the smartphone model versus a portable reference device that indicated FDA/ISO requirements were likely to be met if full testing was conducted.…”
Section: Discussionmentioning
confidence: 99%
“…24 Their results indicated a wide range of adult persons utilized a smartphone model to perform repeated pulse oximeter spot checks with an accuracy and precision equivalent to hospital grade clip sensors. 24 This clinical study had few hypoxemic patients, but did report human steady state hypoxia testing of the smartphone model versus a portable reference device that indicated FDA/ISO requirements were likely to be met if full testing was conducted. 24…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , ...…”
Section: Uncited Referencesunclassified